Methylomic and phenotypic analysis of the ModH5 phasevarion of Helicobacter pylori. Issue 1 (December 2017) - Srikhanta, Yogitha; Gorrell, Rebecca; Power, Peter; Tsyganov, Kirill; Boitano, Matthew; Clark, Tyson; Korlach, Jonas; Hartland, Elizabeth; Jennings, Michael; Kwok, Terry
Abstract TheHelicobacter pylori phase variable genemodH, typified by gene HP1522 in strain 26695, encodes a N6 -adenosine type III DNA methyltransferase. Our previous studies identified multiple strain-specificmodH variants (modH1 –modH19 ) and showed that phase variation ofmodH5 inH. pylori P12 influenced expression of motility-associated genes and outer membrane protein genehopG . However, the ModH5 DNA recognition motif and the mechanism by which ModH5 controls gene expression were unknown. Here, using comparative single molecule real-time sequencing, we identify the DNA site methylated by ModH5 as 5′-Gm6 ACC-3′. This motif is vastly underrepresented inH. pylori genomes, but overrepresented in a number of virulence genes, including motility-associated genes, and outer membrane protein genes. Motility and the number of flagella ofH. pylori P12 wild-type were significantly higher than that of isogenicmodH5 OFF or ΔmodH5 mutants, indicating that phase variable switching ofmodH5 expression plays a role in regulatingH. pylori motility phenotypes. Using the flagellin A (flaA ) gene as a model, we show that ModH5 modulatesflaA promoter activity in a GACC methylation-dependent manner. These findings provide novel insights into the role of ModH5 in gene regulation and how it mediates epigenetic regulation ofH. pylori motility.